The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21037/tlcr-22-644
|View full text |Cite
|
Sign up to set email alerts
|

International consensus on radiotherapy in metastatic non-small cell lung cancer

Abstract: Background: Lung cancer is the leading cause of cancer-related death worldwide, with non-small cell lung cancer (NSCLC) accounting for most cases. While radiotherapy has historically served as a palliative modality in metastatic NSCLC, considerable advances in its technology and the continuous development of cutting-edge therapeutic agents, such as targeted therapy and immune checkpoint inhibitors (ICIs), are increasing its role in the multi-disciplinary management of the disease.Methods: International radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 241 publications
0
6
0
Order By: Relevance
“…There are two types of lung cancer: non-small cell lung cancer (metastatic NSCLC) and small cell lung cancer. 58 Lung cancer has higher morbidity and mortality than most cancers. 59 SLC solely responsible for 10-15% of all lung cancers and yes, the prognosis is very poor.…”
Section: Lung Cancermentioning
confidence: 99%
“…There are two types of lung cancer: non-small cell lung cancer (metastatic NSCLC) and small cell lung cancer. 58 Lung cancer has higher morbidity and mortality than most cancers. 59 SLC solely responsible for 10-15% of all lung cancers and yes, the prognosis is very poor.…”
Section: Lung Cancermentioning
confidence: 99%
“…A meta‐analysis found that addition of radiotherapy to the primary tumor could significantly improve the OS and PFS of patients with oligometastatic NSCLC 10 . In another study, radiotherapy for thoracic diseases resulted in a significant reduction in the risk of death by 56% and in the risk of disease progression by 58%, respectively 11 . Hence, the addition of radiotherapy directed at the primary tumor could confer survival benefits in a selected group of patients with mNSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there has been no evidence from randomized clinical trials supporting which timing is better for survival when integrating TRT into the comprehensive treatment of mNSCLC 11 . A previous retrospective study has indicated that EGFR‐TKI plus earlier TRT (receiving radiotherapy before EGFR‐TKI resistance) achieved better PFS compared with delayed TRT (receiving radiotherapy after progressive disease) in stage IV EGFR ‐mutant NSCLC patients and a lower incidence of radiation pneumonitis 12 .…”
Section: Introductionmentioning
confidence: 99%
“…This was extensively discussed in a recent consensus of international experts on the use of RT in metastatic NSCLC. However, this was agreed that the evidences on the impact of RT on survival come from the trials in which IO was not used (10). Thus still being aware of the impact of IO on survival in metastatic NSCLC, we cannot yet consider these cases as curable.…”
Section: Introductionmentioning
confidence: 99%